Pengaruh Komposisi Media Tanam Terhadap Pertumbuhan Stek Batang Kantong Semar (Nepenthes gracilis Korth.) - Irwan Lovadi, Fadillah Febriani, Riza Linda (Jurnal Protobiont, 2015)
Research on the effect of media composition for the growth of stem cuttings Nepenthes (Nepenthes gracilis Korth.) has been done in Nepenthes captivity Pontianak, Faculty of Mathematics and Natural Scienses and in Chemistry and Soil Fertility Laboratory of the Faculty of Agriculture, University of Tanjungpura in November 2013 until January 2014. This research to determine the effect of planting media composition on the growth of stem cuttings Nepenthes gracilis. This research uses a completely randomized design (CRD) with 7 treatments and 3 replications, as treatments in this experiment is the planting media composition Moss (M0), Moss + Compost (M1), Moss + Coconut Fiber Powder (M2), Moss + Charcoal hust (M3), Moss + Compost + Coconut Fiber Powder (M4), Moss + Compost + Charcoal Husk (M5) and Lumut + Coconut Fiber Powder + Charcoal Husk (M6). Parameters measured were plant height, root length, number of leaves, shoot number, number of bags and wet weight. The results showed that the composition of the planting medium significantly different to the length and number of pockets. The best planting medium composition on the growth of root length Nepenthes gracilis is Lumut + Coconut Fiber Powder + charcoal husk and the best media composition to the amount of bags of Nepenthes gracilis is Lumut + Coconut Fiber Powder. The Effect of media composition was not significantly different planting on plant height, leaf number, number of buds and wet weight